Penerapan Model Problem Solving untuk Optimalisasi Pembelajaran Alat Ukur Kelistrikan: Studi Eksperimental: Application of Problem-Solving Model for Optimization of Electrical Measuring Instrument Learning: Experimental Study - Heru Nuryanto; Achmad Imam Agung; I Gusti Putu Asto Buditjahjanto (ITScience (Information Technology and Science), 2024)
Learning electrical measuring instruments at SMK Bendo Magetan still faces various challenges, especially in understanding theoretical concepts and mastering students' practical skills. This study aims to measure the effectiveness of applying the problem-solving learning model in improving student learning outcomes in electrical measuring instruments, both from cognitive and psychomotor aspects. The research used a pre-experimental design with a one-group pretest-posttest. The subjects of the study consisted of 34 students of class X TPUPT SMKN 1 Bendo Magetan who were selected using the total sampling technique. The research instruments included a multiple-choice objective test of 30 questions to measure conceptual understanding and a practical observation sheet to assess practical skills. Data were analyzed using a learning completeness test, effect size, and normalized gain to comprehensively measure improvements in learning outcomes. The results showed a significant increase in student learning outcomes. The classical completeness analysis achieved the set target, with the effect size in the large category, indicating a strong impact of the applied learning model. The normalized gain test stated an increase in student abilities in the moderate category, especially in mastering the material of electrical measuring instruments. This study states that the problem-solving learning model has proven effective in improving student learning outcomes, conceptual understanding and practical skills. This model helps students understand the concept of electrical measurement in-depth and improves their ability to operate measuring instruments effectively. These findings significantly contribute to developing learning methods in vocational education, especially when facing technical and practical learning challenges.